2004
DOI: 10.1007/s00429-004-0379-0
|View full text |Cite
|
Sign up to set email alerts
|

Palatal shelf movement during palatogenesis: a fate map of the fetal mouse palate cultured in vitro

Abstract: Day-13 fetal mouse palates (plug day=day 0) were labeled with carbon particles at various sites of palatal shelves and cultivated in a chemically defined medium for up to 48 h. During the culture period, the bilateral palatal shelves came in contact and fused with each other, which simulated in vivo palatogenesis. The carbon study revealed that at the midpalatal region, the medial edge of the palatal shelf elevated to the horizontal plane, elongated toward the midline, and made contact with the medial edge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
(31 reference statements)
1
34
0
Order By: Relevance
“…The methods vary in their ability to stimulate palate development and fusion, and the organ culture has significant advantages in this regard (Chou et al, 2004). In the current study, we observed that Dex appeared to stimulate the thickening of the MEE.…”
Section: Fig1 Hematoxylin and Eosin (H And E)-stained Sections Of The supporting
confidence: 58%
“…The methods vary in their ability to stimulate palate development and fusion, and the organ culture has significant advantages in this regard (Chou et al, 2004). In the current study, we observed that Dex appeared to stimulate the thickening of the MEE.…”
Section: Fig1 Hematoxylin and Eosin (H And E)-stained Sections Of The supporting
confidence: 58%
“…Thus, comparisons of the mid-palatal region during palatal fusion with the anterior and posterior regions were an important objective of our study. The anterior and posterior regions of the palate have been reported to fuse mainly by tissue remodeling, whereas the mid-palate closes mainly by medial elongation of the shelf [Chou et al, 2004;Okano et al, 2006]. Periostin was present in the mesenchyme with higher levels of expression in the far anterior and posterior region compared with other regions.…”
Section: Discussionmentioning
confidence: 82%
“…In some reports regarding the patterned formation of palatal rugae development, morphogenesis, gene expression patterns, and cellular modulations have been examined partially and separately (Peterkova et al 1987;Sakamoto et al 1989;Takanosu et al 2002;Motabagani 2006;Charles et al 2007;Gritli-Linde 2007). Although one previous study has shown the critical movement patterns of palatal shelves by using carbon particle transplantations during in vitro organ cultivation of the palate, the investigation only mentions the palatal fusion mechanism (Chou et al 2004). In addition, cellular events in rugae-forming regions have been studied together with region-specific proliferation and apoptosis patterns in two separate regions designated as the ruga ridge and the inter-rugae (Luke 1984;Amasaki et al 2002Amasaki et al , 2003Takanosu et al 2002).…”
Section: Introductionmentioning
confidence: 96%